Germany : Financial Sector Assessment Program Technical Note-Macroprudential Policy Framework And Tools. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
Germany's macroprudential policy framework and toolkit are well developed. The FSAP found the institutional arrangements for macroprudential policy to be mostly sound and operating well. Capacity and expertise in risk monitoring is good, thanks to the analytical power and data access of the central bank, and close coordination between the macro- and microprudential arms of the financial supervisory authorities. Germany's macroprudential toolkit continues to develop. The principal outstanding task is to add powers to set caps on debt-to-income and debt service-to-income ratios on residential real estate loans to the already-established powers over loan-to-value ratios and amortization rates. These additions will place Germany's toolkit on a par with its peers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Germany